Data Management. Data, Data Everywhere 24th British National Conference on Databases, BNCOD 24, Glasgow, UK, July 3-5, 2007. Proceedings - Cooper, Richard; Kennedy, Jessie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
BNCOD has, for the past 27 years, provided a forum for researchers world-wide to gather to discuss the topical issues in databaseresearch.As the researchch- lenges have evolved, so BNCOD has changed its topics of interest accordingly, now covering data management more widely. In doing so, it has evolved from a local conference mostly attended by British researchers to a truly international conference that happens to be held in Britain. This year, for instance, sign- cantly less than half of the presentations are from UK or Irish authors, other contributions coming from continental Europe, Asia and the USA. Currently, one of the most pressing challenges is to ?nd ways of evolving database technology to cope with its new role in underpinning the massively distributed and heterogeneous applications built on top of the Internet. This has a?ected both the ways in which data has been accessed and the ways in which it is represented, with XML data management becoming an important issue and, as such, heavily represented at this conference. It has also brought back issues of performance that might have been considered largely solved by the improvements in hardware, since data now has to be managed on devices of low power and small memory as well as on standard client and powerful server machines. We therefore invited papers on all aspects of data management, particularly relatedtohowdataisusedintheubiquitousenvironmentofthemodernInternet bycomplexdistributedandscienti?capplications.Ofthe56submissionsfrom14 countriesweselected15fullpapers,3shortpapersand7postersforpresentation, all of which appear in this volume along with 2 invited papers.
Invited Papers -- Design Abstractions for Innovative Web Applications -- Automation Everywhere: Autonomics and Data Management -- Data Applications -- Exhaustive Peptide Searching Using Relations -- Data Lineage Tracing in Data Warehousing Environments -- Fast Recognition of Asian Characters Based on Database Methodologies -- SPDBSW: A Service Prototype of SPDBS on the Web -- Searching XML Documents -- Indexing and Searching XML Documents Based on Content and Structure Synopses -- PosFilter: An Efficient Filtering Technique of XML Documents Based on Postfix Sharing -- OOXSearch: A Search Engine for Answering Loosely Structured XML Queries Using OO Programming -- Querying XML Documents -- Evaluating XPath Queries on XML Data Streams -- PSMQ: Path Based Storage and Metadata Guided Twig Query Evaluation -- Parameterized XPath Views -- XML Transformation -- Specifying and Optimising XML Views -- Isolating Order Semantics in Order-Sensitive XQuery-to-SQL Translation -- Poster Papers -- Representation and Management of Evolving Features in OS MasterMap ITN Data -- Hopfilter: An Agent for Filtering Web Pages Based on the Hopfield Artificial Neural Network Model -- A New Approach to Connecting Information Systems in Healthcare -- XML Query Result Size Estimation for Small Bandwidth Devices -- An Efficient Sheet Partition Technique for Very Large Relational Tables in OLAP -- A Method of Improving the Efficiency of Mining Sub-structures in Molecular Structure Databases -- XFLab: A Technique of Query Processing over XML Fragment Stream -- Clustering and Security -- Knowledge Discovery from Semantically Heterogeneous Aggregate Databases Using Model-Based Clustering -- Speeding Up Clustering-Based k-Anonymisation Algorithms with Pre-partitioning -- Fine-Grained Access Control for Database Management Systems -- Data Mining and Extraction -- Extracting Temporal Information from Short Messages -- Max-FTP: Mining Maximal Fault-Tolerant Frequent Patterns from Databases -- A New Approach for Distributed Density Based Clustering on Grid Platform.
Keywords: Computer science; Data structures (Computer science).; Database management; Information storage and retrieval; Computer Science; Data Structures, Cryptology and Information Theory; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Electronic books